Lessons from Brazil: Opportunities of Bioethanol Biofuel in Indonesia - Ibham Veza; Djati Wibowo Djamari; Nur Hamzah; Noreffendy Tamaldin; Mairizal Mairizal; Handi Handi; Yusrizal Yusrizal; Ridwan Usman (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2022)
Brazil has a long tradition of bioethanol production from sugarcane. Following the Middle East crisis in the 1970s, the oil price increased twofold, doubling Brazil’s spending on oil imports. As a result, the country had to find an alternative type of fuel to reduce its expenditure on conventional petrol fuels. With its vast tropical land conditions, the Brazilian government then put massive effort to establish the infrastructure and research of bioethanol from 1975 and 1989. Research plays a pivotal role in the success of Brazil’s ethanol industry. The country was heavily criticised at the beginning of the programme, but today, Brazil is the second-largest ethanol producer after the USA. Brazil produces the cheapest ethanol in the world and does not depend on fossil fuel to supply its energy demand. Indonesia and Brazil share the same landscape and geographical advantages. This paper aims to discuss the success of the Brazilian bioethanol industry and draw important lessons from it. In a nutshell, Indonesia should increase bioethanol production from renewable sources. Also, the modernization of distilleries facilities, the establishment of new production plants, the introduction of subsidies and the reduction of taxes for ethanol producers are needed. In summary, apart from massive research and development, we concluded that effective and strong long-term government commitment play important role in shaping the future of the Indonesian bioethanol industry.